2015
DOI: 10.3389/fnana.2015.00136
|View full text |Cite
|
Sign up to set email alerts
|

LIM homeobox protein 5 (Lhx5) is essential for mamillary body development

Abstract: The mamillary body (MM) is a group of hypothalamic nuclei related to memory and spatial navigation that interconnects hippocampal, thalamic, and tegmental regions. Here we demonstrate that Lhx5, a LIM-HD domain transcription factor expressed early in the developing posterior hypothalamus, is required for the generation of the MM and its derived tracts. The MM markers Foxb1, Sim2, and Lhx1 are absent in Lhx5 knock-out mice from early embryonic stages, suggesting abnormal specification of this region. This was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…For instance, Lhx5 , a gene expressed in NP cells when contacting DE, is known to promote forebrain development by regulating the Wnt signaling pathway ( 33 ). Knockdown of Lhx5 resulted in apoptotic hypothalamic development ( 49 ). Nkx2-1, another gene expressed in NP cells when contacting DE, is also recognized for its role in response to dorsal–ventral patterning in the neural tube and for specifying cortical interneuron subtypes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lhx5 , a gene expressed in NP cells when contacting DE, is known to promote forebrain development by regulating the Wnt signaling pathway ( 33 ). Knockdown of Lhx5 resulted in apoptotic hypothalamic development ( 49 ). Nkx2-1, another gene expressed in NP cells when contacting DE, is also recognized for its role in response to dorsal–ventral patterning in the neural tube and for specifying cortical interneuron subtypes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, at stage 32 (present results), the NLT is negative for the markers considered here, although it is positive for ScLhx5 at previous stages ( Santos-Durán et al, 2018 ). Similarly, the mammalian ventromedial nucleus seems to be positive for Lhx5 and abuts Dlx -expressing territories at early stages ( Sheng et al, 1997 ; Abellán et al, 2010 ), but it is negative at later stages ( Szabó et al, 2009 ; Heide et al, 2015 ; Miquelajáuregui et al, 2015 ). The catshark NLT presents several types of peptidergic cells (somatostatin, Sobrido-Cameán et al, 2020 ; met-enkephalin and leu-enkephalin, Vallarino et al, 1994 ; melanin-concentrating hormone, Vallarino et al, 1989a ; atrial natriuretic factor, Vallarino et al, 1990b ; delta sleep-inducing peptide, Vallarino et al, 1992 ; beta-endorphin, Vallarino et al, 1989b ; galanin, Vallarino et al, 1991 ; neuropeptide Y, Vallarino et al, 1988 ; corticotropin-releasing factor, Vallarino et al, 1989c ; adrenocorticotropic hormone, Vallarino and Ottonello, 1987 , Vallarino et al, 1989b ), and is thought to be associated with the hypophysis, as reported in actinopterygian fishes (reviewed in Butler and Hodos, 2005 ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Lhx5 , a gene expressed in NP cells when contacting DE, is known to promote forebrain development by regulating the Wnt signaling pathway (32). Knockdown of Lhx5 resulted in apoptotic hypothalamic development (46). Nkx2-1 , another gene expressed in NP cells when contacting DE, is also recognized for its role in response to dorsal-ventral patterning in the neural tube and for specifying cortical interneuron subtypes (33).…”
Section: Discussionmentioning
confidence: 99%